Changes in match duration in badminton Superseries tournaments - Iizuka, T.; Hirano, K.; Ugaya, M. (Sports Science in Elite Athlete Support, 2017)
In 2006, the Badminton World Federation (BWF) changed the scoring system in badminton to a 21 points × 3 games rally-point scoring system, intending to shorten the duration of matches. However, as the match duration in recent international tournaments is once again increasing, BWF is considering making further changes to the scoring system. In this paper, we examine the changes in match duration in international tournaments since the new scoring system was implemented in 2006. This analysis was performed by comparing the duration of matches from twelve Superseries tournaments during the 2008 Beijing Olympic Games qualification period and the 2016 Rio de Janeiro Olympic Games qualification period. As a result, it was found that the durations of the matches for the Superseries tournaments during the latter period had significantly increased from the former period. A further analysis was conducted to compare match characteristics between the Japan Open Superseries in 2007 and 2015, held during the Beijing and Rio de Janeiro Olympic Games qualification periods, respectively. It was shown that rally time in men`s and women`s singles events and rest time in all events were significantly longer in Japan Open 2015 as compared to 2007. Therefore, it is suggested that the increase in rest time as well as rally time were associated with longer duration of matches in Superseries tournaments during the Rio de Janeiro Olympic Games qualification period.